Microneedle-Assisted Drug Delivery: Minimally Invasive Approach for Transdermal Therapeutics - Pratiksha Ramdas Bij; Aakanksha Andani Gaikwad; Ashwini Buddhiwan Hiwale; Anusha C K; Ganavi Maheshappa Halageri (Asian Journal of Pharmaceutical Research and Development, 2026)
Microneedle-assisted drug delivery has emerged as a promising advancement in transdermal therapeutic systems, addressing the limitations of conventional oral, injectable, and topical routes. Traditional transdermal drug delivery systems are restricted by the skin’s outermost barrier, the stratum corneum, which limits the permeation of most drugs, particularly macromolecules such as proteins and peptides. Microneedles, typically ranging from 50 to 900 µm in length, overcome this barrier by creating transient microchannels in the skin, enabling painless and minimally invasive drug delivery without reaching dermal nerves. This review provides a comprehensive overview of microneedle technology, including skin anatomy, types of microneedles, materials used, fabrication techniques, and mechanisms of drug delivery. Various microneedle systems-such as solid, coated, dissolving, hollow, and hydrogel-forming-offer diverse strategies for controlled and targeted drug administration. Materials ranging from metals and silicon to polymers and carbohydrates significantly influence performance, biocompatibility, and scalability. Microneedles have demonstrated wide-ranging applications in vaccine delivery, diabetes management, cancer therapy, pain management, dermatology, and the delivery of proteins, peptides, and genetic materials. Key advantages include improved patient compliance, avoidance of first-pass metabolism, enhanced drug permeation, and reduced risk of needle-stick injuries. However, challenges such as limited drug loading, mechanical strength issues, manufacturing complexity, and regulatory barriers remain. Recent advances, including smart stimuli-responsive systems, biosensor integration, 3D printing, and AI-based optimization, have further expanded the potential of microneedles. Despite existing limitations, microneedle technology holds significant promise for future healthcare, particularly in personalized medicine, wearable drug delivery, and global vaccination strategies.